THE ROLE OF SOCIETY IN THE MEASURE OF ENVIRONMENT PROTECTION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2007)
The paper analyzes preconditions of launching the environment education in Latvia. Since the environment has become a social priority, policies of sustainability have come to form a part of the agenda in modern society. Universities play a vital role in the success of these policies and are a key factor, alongside political and economic factors, in guaranteeing sustainable development.The study develops an alternative formula expert method that integrates evaluation and evaluation, maximizes fairness, broadly encompasses the key tree, tree-environment and tree-human traits, and accords realistic monetary value.The influence of universities is confirmed by the extent to which society needs a human capital that is able to meet the challenge of sustainability. However, it should be understood that Universities create opinions and methodological paradigms that should lead the social progress.